Does supplementation with mitochondria improve oocyte competence? A systematic review. Issue 3 (March 2021) - Ferreira, Ana Filipa; Soares, Maria; Almeida Reis, Sandra; Ramalho-Santos, João; Sousa, Ana Paula; Almeida-Santos, Teresa
Abstract : Mitochondrial supplementation was proposed as a complementary treatment to assisted reproductive technologies to improve oocyte competence and support post-fertilization development. This strategy is based on the fact that poor-quality/aged oocytes contain lower and dysfunctional mitochondria. However, the efficacy and safety of mitochondrial supplementation are still controversial. Therefore, this review summarizes the clinical/biological outcomes of mitochondrial supplementation, aiming to improve oocyte competence or explore the safety of this technique, and was based on an online search using PubMed and Web of Science, until September 2019. The studies included reported outcomes related to the efficacy and safety of mitochondrial supplementation either in human or animal models (bovine, porcine and mouse). Extracted data were organized according to study objective, the mitochondrial source and the main outcomes: fertilization/pregnancy rates, embryo development and adverse outcomes. Clinical pregnancy was not improved in the only randomized controlled trial published, although an increase was demonstrated in other non-randomized studies. Fertilization rate and embryo development were not different from control groups in the majority of studies, although performed in different contexts and using diverse sources of mitochondria. The safety of mitochondria transfer is still a concern, however, the euploid rate and the absence of reported congenital malformation from the clinical studies are reassuring. In summary, mitochondrial supplementation does not seem to cause harm although the benefit of improving oocyte competence is still unclear due to the diversity of methodological approaches and low-quality of the data available. Analyzed data support the need to investigate further, in both pre-clinical and clinical contexts.